Anti-Inflammatory and Cytostatic Activities of a Parthenolide-Like Sesquiterpene Lactone from Cota palaestina subsp. syriaca - Talhouk, Rabih S. (Hindawi Publishing Corporation, 2015)

(untitled) (Evid Based Complement Alternat Med)
A sesquiterpene lactone 1-β,10-Epoxy-6-hydroxy-1,10H-inunolide (K100) was isolated through “bioassay-guided fractionation” from Cota palaestina subsp. syriaca, an Eastern Mediterranean endemic plant. K100 inhibited endotoxin- (ET-) induced proinflammatory markers: IL-6, MMP-9, and NO in normal mouse mammary SCp2 Cells. Molecular docking in silico suggested that K100, having highly analogous structure as parthenolide (PTL), an anticancer compound, could bind PTL target proteins at similar positions and with comparable binding affinities. Both compounds, K100 and PTL, inhibited the proliferation and prolonged the S-phase of the cell cycle of breast adenocarcinoma MDA-MB-231 cells grown in 2D cultures. Noncytotoxic concentrations of K100 and PTL decreased the proliferation rate of MDA-MB-231 and shifted their morphology from stellate to spherical colonies in 3D cultures. This was accompanied with a significant increase in the amount of small colonies and a decrease in the amount of large colonies. Moreover, K100 and PTL decreased cellular motility and invasiveness of MDA-MB-231 cells. In summary, these results suggest that K100 exhibits PTL-analogous anti-inflammatory, cytostatic, and antimetastatic effects.